Home security monitoring system with IoT-based Raspberry Pi - I Gusti Made Ngurah Desnanjaya; I Nyoman Alit Arsana (Institute of Advanced Engineering and Science, 2021)
Home security monitoring system is a system that is able to monitor the house from unwanted events such as theft. Home monitoring systems can monitor and send users notices about the condition of their homes at the same time. Notifications sent in the form of pictures of the state of the room in the house, temperature conditions and gas density conditions. The home security monitoring system was created using Raspberry Pi as the control center of the system. It was connected with several sensors namely PIR sensor is used to detect objects that enter the room, raspicam is used to take pictures when the PIR sensor detects objects, temperature sensors and gas sensors are used to detect the state of temperature and gas concentration, and telegram is used as a liaison application to send notifications from Raspberry Pi to tool users. The final result of this research is to build a home security monitoring system with Raspberry Pi based on telegraph messenger. This system is able to monitor the security of the house from burglars or intruders, notify the temperature of the house and detect smoke or gas.